EFFECT OF MINIMIZING SOIL TILLAGE ON MOISTURE SUPPLY AND SPRING BARLEY PRODUCTIVITY IN THE ZONE OF THE LEFT-BANK FOREST-STEPPE OF UKRAINE - Hanhur, V. V.; Len, O. I.; Hanhur, N. V. (Scientific Progress & Innovations, 2021)
Spring barley (Hordeum vulgare L.) is currently one of the important cereals for food and fodder. Under today’s conditions, the issue of increasing crop yields while reducing material and technical costs is espe-cially relevant. The purposeful management of plants’ growth and development is possible using a certain set of factors, including a system of quality and timely tillage. The aim of the research was to find out the influence of different methods of basic soil tillage on water consumption and productivity of spring barley in the Left Bank Forest-Steppe. Determining moisture content of a meter soil layer at the time of sowing spring barley has shown that under No-till systems, the content of available moisture in the layer of 0–100 cm was 8.8 mm or 5.3 % higher as compared with the classical soil tillage. At shallow tillage to a depth of 10–12 cm and surface tillage to a depth of 6–8 cm in the Min-till system, the available moisture content was almost at the level of classical tillage. The tendency was similar at harvesting time. The influence of the main tillage variants on the indicators of spring barley harvest structural elements has been detected. With the classical tillage, the number of productive stems was the highest and exceeded the variants of the minimum tillage by 12–73 pcs/m2 or 2.2–15.7 %. The experiment did not reveal a significant effect of tillage variants on the length and number of grains in the spike. The maximum crop yield (4.16 t/ha) was obtained by carry-ing out shelf plowing to a depth of 20–22 cm under spring barley. With the minimum tillage (depth of 10–12 cm) and Mini-till technology, the crop productivity was by 0.13–0.17 t/ha or 3.4–4.1 % less in comparison with the technology of classical tillage. Under No-till system, a significant decrease in barley grain yield as compared with shelf plowing to a depth of 20–22 cm was observed during 2016–2018, and in 2019–2020 of the studies, the difference between these variants in terms of productivity was within the LSD (least signifi-cant difference).